Issues of Gender Equality in Modern Uzbekistan - Begzod Kushbakovich, Sangirov; Ijod Narzikul Ogli, Akhmedov; Maqsuda Pulatovna, Ergasheva (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the situation of gender equality in the world, especially in Uzbekistan, in recent years, one of the main problems of human society. Also, the origin, study, solutions, and achievements of the concept of gender are reflected in scientific work. Uzbekistan has been reforming its gender equality in recent years. The role and importance of women in society and their participation in projects in the field are growing. In conclusion, ensuring gender equality contributes to the socio-economic and political development of a society.